2015
DOI: 10.1002/cpdd.219
|View full text |Cite
|
Sign up to set email alerts
|

Relative Bioavailability of a Single Dose of Belimumab Administered Subcutaneously by Prefilled Syringe or Autoinjector in Healthy Subjects

Abstract: Intravenous belimumab is approved for the treatment of systemic lupus erythematosus; subcutaneous self‐administration would enable greater patient access. This study assessed relative bioavailability, tolerability, and safety of 1 subcutaneous dose of self‐administered belimumab by healthy subjects using a single‐use autoinjector or prefilled syringe. Subjects (randomized 1:1:1:1) self‐administered belimumab 200 mg subcutaneously (abdomen or thigh) by prefilled syringe or autoinjector. Pharmacokinetics, advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Patients with active SLE demonstrated a good level of usability and reliability with the autoinjector, confirming results of a previous study conducted in healthy subjects [15]. The majority of injection failures was due to user error, which were rectified with additional training and slight adjustments in user instructions.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Patients with active SLE demonstrated a good level of usability and reliability with the autoinjector, confirming results of a previous study conducted in healthy subjects [15]. The majority of injection failures was due to user error, which were rectified with additional training and slight adjustments in user instructions.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the PK results from this study support a 1 – 4-week interval for switching between belimumab IV and belimumab SC. In addition, the stable transition from IV to SC dosing demonstrated here supports the use of the prefilled syringe for administration of belimumab SC as bioequivalent exposures have been demonstrated for belimumab SC administration using the autoinjector and the prefilled syringe [15]. The 200-mg dose was selected based on previous analyses that showed that weekly belimumab 200 mg SC would achieve similar steady-state belimumab exposures to that of monthly belimumab 10 mg/kg IV [16].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A liquid formulation of belimumab has been developed, along with a prefilled syringe and an autoinjector device for administering belimumab SC. In a single‐dose study, healthy volunteers self‐administered belimumab 200 mg SC using the prefilled syringe or the autoinjector device; both injection devices demonstrated good usability, reliability, and safety . The 200 mg SC dose was selected in order to achieve a target belimumab steady‐state area under the curve exposure following SC administration similar to that obtained with 10 mg/kg IV every 4 weeks .…”
mentioning
confidence: 99%
“…The development of a novel liquid formulation of belimumab, along with a prefilled syringe and autoinjector device, enables patients to self-administer subcutaneous (SC) belimumab, an option demonstrated as preferable to IV administration by the majority of individuals (12). Single-and multi-dose studies of self-administered SC belimumab 200 mg have demonstrated that both the prefilled syringe and autoinjector devices show good usability, reliability, and safety (13,14). Furthermore, administration of weekly SC belimumab 200 mg achieved a target belimumab steady-state exposure similar to that obtained with IV belimumab 10 mg/kg every 4 weeks (15,16).…”
mentioning
confidence: 99%